When waiting means trouble: an enquiry into the approach toward prevention against jihadism in Senegal - Bangura, Ibrahim; Owusu, Augustine; Quaye, Andrea Samantha (Frontiers in Political Science, 2024)
In the last decade, West Africa has experienced increased activities by Jihadist groups, especially after the fall of the Muammar Qaddafi regime in Libya in 2012. The activities of these groups have gradually spread in the region, with countries such as Mali and Burkina Faso experiencing continued attacks. Taking the current socio-economic, religious and political context of Senegal into consideration, this study interrogates the factors that have so far prevented attacks by Jihadist groups in Senegal, the role that women and youth could play in mitigating jihadism in Senegal, and how the existing social capital in the country, could be further mobilised to foster trust building and social cohesion, thereby enhancing the prevention of violent extremism in the country?. Furthermore, the study explores the need for a regional approach in dealing with the existing and emerging threats posed by Jihadist activities in the region. Methodologically, this study uses interviews and Focus Group Discussions to collect primary data from government officials, academics, civil society and international development partners. Secondary data from a wide range of sources are used to analyse the case of Senegal.